Perlindungan Hukum Persaingan Usaha Terhadap Indikasi Persekongkolan Tender Jack Up Drilling Rig Services Antara HUSKY-CNOOC MADURA LIMITED Dengan PT COSL INDO (Analisis Putusan KPPU No. 03/KPPU-L/2016) - suradiyanto suradiyanto; Dinny Wirawan Pratiwie (Yuriska: Jurnal Ilmiah Hukum, 2020)
Conspiracy use various way for coordinate activities they like through settings production, determination price horizontally, collusive tendering, division area, division consumer as a non-territorial, and division share market, even though similarly we need realize it that effective conspiracy it is not easy for achieved. However there trend the perpetrators business will always attempted maximizing profit his company respectively. Must there is some requirement in occurrence a conspiracy is must existence deal agreement or collusion between perpetrators effort. There is two form collusion in conspiracy, namely: collusion explicit, where the member communicate and coordinate deal they on real/live can declared with some document agreement already they agree, the data regarding the joint audit, management conspiracy, policies-policies writing, sales data and other data. There is also collusion secretly, where the perpetrators business member conspiracy no communicate on blatant, usually meetings too held on secret. And regular use as the media is association industry, so meetings member conspiracy camouflaged with legal meetings such as meeting associations. Form the second collusion this very difficult for detected by enforcer law. However experience from various country prove that at least 30% of conspiracy is involve associations.